Women's Visibility in Decision Making Processes in Africa—Progress, Challenges, and Way Forward - Ilesanmi, Oluwatoyin Olatundun (Frontiers in Sociology, 2018)
The issue of women’s marginalization and invisibility in decision-making in Africa remains a continual concern on international discourse. These are likely due to restrictive laws, cultural diversities, and practices, institutional barriers, as well as disproportionate access to quality education, healthcare and resources. Reversing these discriminatory practices is not impossible if the right mechanisms are enshrined across the continent. The process towards increasing the visibility of women in decision-making across the continent requires an understanding of the progress made so far, the challenges and the way forward. In consequence, this paper conducted a review of the literature to determine the major organs of decision-making in Africa, the current status of African women and women organizations in decision-making, existing institutional policies demanding female participation in decision-making in Africa, and barriers to women participation in the decision-making process in Africa. It also made recommendations for accelerating the way forward in view of Agenda 2030.